1985
DOI: 10.1007/bf00044062
|View full text |Cite
|
Sign up to set email alerts
|

The small-scale pattern of Cynodon dactylon in Mediterranean pastures

Abstract: The abundance of Cynodon dactylon was recorded in 50 plots presenting different geomorphological conditions and along a transect of 16 500 2 x 2 cm contiguous quadrats within a small basin 330 m in length, in the granite pediment of the Sierra de Guadarrama (Central Spain). Soil analyses were undertaken on samples from the 50 plots and the soil information matrix obtained was analysed using Principal Components Analysis and Discriminant Analysis. Results showed that in the Mediterranean pastures Cynodon dactyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The information theory used by Bartha et al is after Juhasz-Nagy (1984) and is related to BQC. Analyses that relate to the plant's-eye view are in bold Amarasinghe & Pemadasa (1982) 1.0 Transect of cells BQV, BQC Zamfir et al (1999) 1.0 Transect of cells DCA De Pablo et al (1982) 0.64 Transect of cells H(E.P) Mahdi & Law (1987) 0.28, 0.13, 0.03 Separate plant-centred areas Densities within areas Kershaw (1962) 0.25 Transect of cells BQV, BQC Gibson & Greig-Smith (1986) 0.25 Transect of cells BQV Gibson (1988) 0.25 Transect of cells TTLQV, 3TLQV, TTLCA, DCA Bartha et al (1995) 0.25 Transect of cells Information theory Edwards et al (1996) 0.25 Transect of cells TTLQV Stowe & Wade (1979) 0.16 Transect of points J Agnew & Gitay (1990) 0.16 Transect of cells TTLQV Kershaw (1958Kershaw ( , 1959 0.05 Transect of points BQV, interspecific correlations Kershaw & Tallis (1958) 0.05 Transect of points BQV, interspecific correlations Turkington & Harper (1979) 0.05 Transect of points BQC Galiano (1985Galiano ( , 1986 0.04 Transect of cells BQV Wilson et al (1987) 0.04 Transect of cells Variance in species richness Van der Hoeven et al (1990) 0.04 Grid of cells Lagged Moran's I Van Rijnberk & During (1990) 0.016 Grid of points Z-correlograms Watkins & Wilson (1992) 0.016 Grid of cells Variance in species richness Thórhallsdóttir (1990b) 0.0078 Transect of points J Law et al (1993) 0.0078 Grid of points Neighbour identities…”
Section:     mentioning
confidence: 99%
“…The information theory used by Bartha et al is after Juhasz-Nagy (1984) and is related to BQC. Analyses that relate to the plant's-eye view are in bold Amarasinghe & Pemadasa (1982) 1.0 Transect of cells BQV, BQC Zamfir et al (1999) 1.0 Transect of cells DCA De Pablo et al (1982) 0.64 Transect of cells H(E.P) Mahdi & Law (1987) 0.28, 0.13, 0.03 Separate plant-centred areas Densities within areas Kershaw (1962) 0.25 Transect of cells BQV, BQC Gibson & Greig-Smith (1986) 0.25 Transect of cells BQV Gibson (1988) 0.25 Transect of cells TTLQV, 3TLQV, TTLCA, DCA Bartha et al (1995) 0.25 Transect of cells Information theory Edwards et al (1996) 0.25 Transect of cells TTLQV Stowe & Wade (1979) 0.16 Transect of points J Agnew & Gitay (1990) 0.16 Transect of cells TTLQV Kershaw (1958Kershaw ( , 1959 0.05 Transect of points BQV, interspecific correlations Kershaw & Tallis (1958) 0.05 Transect of points BQV, interspecific correlations Turkington & Harper (1979) 0.05 Transect of points BQC Galiano (1985Galiano ( , 1986 0.04 Transect of cells BQV Wilson et al (1987) 0.04 Transect of cells Variance in species richness Van der Hoeven et al (1990) 0.04 Grid of cells Lagged Moran's I Van Rijnberk & During (1990) 0.016 Grid of points Z-correlograms Watkins & Wilson (1992) 0.016 Grid of cells Variance in species richness Thórhallsdóttir (1990b) 0.0078 Transect of points J Law et al (1993) 0.0078 Grid of points Neighbour identities…”
Section:     mentioning
confidence: 99%
“…Climate (Barbour and Billings 1998) and disturbance regimes (Grime 1979) are responsible for regional-scale patterns, whereas species interactions (Smith and Huston 1989;Holmgren et al 1997) and spatial heterogeneity of environmental factors such as topography (Greig-Smith 1961), soil depth (Kershaw 1959), and soil nutrients (Galiano 1985) may be responsible for patterns at local scales. In addition, past processes such as disturbance (Crawley 1986) may act independently or in concert with ongoing processes such as competition (Keddy 2001) or facilitation (Smith and Huston 1989;Bruno et al 2003) to affect the abundance and distribution of plants at a variety of scales.…”
Section: Introductionmentioning
confidence: 99%
“…Another study conducted in the same paddock as in the current study indicated that the spatial variability in pre-grazing herbage mass in the early grazing season (May) mainly reflected the variability in herbage production after the initiation of spring growth, which may have reflected the spatial variability in soil nutrients and/or moisture (Hirata et al 2007). Spatial variabilities in the chemical, physical and biological attributes of soil and their association with vegetation have been widely reported for grasslands (Rogers and King 1972;Galiano 1985;McNaughton and Banyikwa 1995;Ritz et al 2004). From the above facts, we interpret that the spatial heterogeneity in herbage mass was created in the paddock every year by the first grazing period through the spatially fixed heterogeneity in soil-related factors, and was maintained until the last grazing period mainly by herbivory by animals.…”
Section: Discussionmentioning
confidence: 91%